2022
DOI: 10.2196/35860
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Thrombotic Complication Risk Factors Associated With COVID-19 via Heterogeneous Patient Data: Retrospective Observational Study

Abstract: Background COVID-19 has been observed to be associated with venous and arterial thrombosis. The inflammatory disease prolongs hospitalization, and preexisting comorbidities can intensity the thrombotic burden in patients with COVID-19. However, venous thromboembolism, arterial thrombosis, and other vascular complications may go unnoticed in critical care settings. Early risk stratification is paramount in the COVID-19 patient population for proactive monitoring of thrombotic complications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is observed that infected patients can present different manifestations and results, especially when considering the oncological disease. Therefore, it is essential to identify, through studies, the main characteristics of those infected in order to help allocate the right resources and improve the quality of care [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that infected patients can present different manifestations and results, especially when considering the oncological disease. Therefore, it is essential to identify, through studies, the main characteristics of those infected in order to help allocate the right resources and improve the quality of care [ 7 ].…”
Section: Introductionmentioning
confidence: 99%